(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Islamic banking complies with Islamic law known as Shariah, in which payment and receipt ofinterest is strictly prohibited and the business is based on the profit sharing. Trading in debts is also notallowed. Islamic banking encourages the financial inclusion by giving interest free loans. Islamic bankingis currently growing at the rate of 20 annually and comprises 400 institutions with assets undermanagement in excess of US 1 trillion. Because of the significant requirement of capital in the country,there is wider scope for adoption of Islamic banking in India. Islamic banking will attract FDIs from golfcountries, offering sustainable development and ensuring inclusive growth. At 47, credit-deposit ratioamong Muslims in India is lower than the national average of 74 (outlook India, 2010). There is aconflicting situation mainly between the Shariah law and Indian Banking Act, 1949. So it is essential toevaluate the regulatory framework, instruments used and future potential of Islamic banking in India. Thepresent study is an attempt to explore the basic knowledge and challenges faced by Islamic banking inIndia.